COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) – BASED INTERACTIVE CD IN TEACHING READING - Mubarok, Husni; Effendi, Dwi Erlin; Sofiana, Nina (Universitas Negeri Semarang, 2016)
This paper was aimed at describing students’ activities during the implementation of teaching reading through CIRC-based interactive CD, knowing students’ achievement in reading after taught by using the media, and their responses toward the implementation of the media. This study was conducted on nine different junior high schools in Jepara. The subject of the study was seventh grade students. The research method of this study was classroom action research in which the researchers used observation, test, and questionnaire. Observation was used to collect the data dealing with students’ activities in the classroom. Test was used to measure students’ achievement before the implementation, first cycle and second cycle. Questionnaire was used to get students’ responses toward the implementation of the media. The result showed that there were some activities in teaching reading like reading group and team and basal-related activities. The improvement of students’ score was also improved before and after the implementation. It was showed by the students’ average score 7.6 (before), 7.8 (first cycle), and 8.0 (second cycle). Students’ perception toward reading was also changed in the aspect of reading nature, learning reading, strange with vocabulary, getting main idea, and teaching media.